Absence/hypoplasia of tibia, polydactyly, retrocerebellar arachnoid cyst, and other anomalies: an autosomal recessive disorder. Issue 11 (November 1995) - Holmes, L B; Redline, R W; Brown, D L; Williams, A J; Collins, T
Abstract : Absence or hypoplasia of the tibia has been reported to occur as an isolated hereditary malformation as well as a feature of several autosomal recessive and autosomal dominant syndromes. We report three sibs with absence or hypoplasia of the tibia in association with other malformations whose parents are first cousins once removed. These infants appear to have a "new" autosomal recessive syndrome.